All Days 2016
DOI: 10.2118/184067-ms
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Nanomaterials on the Rheological and Filtration Properties of Water-Based Drilling Fluids

Abstract: Nanomaterials are the new additives for drilling fluids that can improve its properties and eliminate problems due to increased downtime and well costs. The objective of this research is to select the optimum concentration of nanoparticles that enhance drilling fluid properties and hydraulics. This study investigates the effects of commercially available nanoparticles on the rheological and filtration properties and optimizes the hydraulics of water-based drilling fluids. In this study, the samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 14 publications
1
33
0
1
Order By: Relevance
“…They performed also a cost analysis that showed the economic feasibility of the use of such new fluid. Salih et al [25] stated that use of nanosilica NP in the range of 0.1-0.3 wt % had the most significant impact on the mud properties than any other concentration they have tested (>0.5 wt %). Furthermore they claimed that smart water-based muds with nanosilica can replace oil-based mud in horizontal, directional, and shale drilling operations due to the ability of the newly formed fluid to reduce drilling and production problems.…”
Section: Experimental Studiesmentioning
confidence: 97%
See 1 more Smart Citation
“…They performed also a cost analysis that showed the economic feasibility of the use of such new fluid. Salih et al [25] stated that use of nanosilica NP in the range of 0.1-0.3 wt % had the most significant impact on the mud properties than any other concentration they have tested (>0.5 wt %). Furthermore they claimed that smart water-based muds with nanosilica can replace oil-based mud in horizontal, directional, and shale drilling operations due to the ability of the newly formed fluid to reduce drilling and production problems.…”
Section: Experimental Studiesmentioning
confidence: 97%
“…The NWBM based on CuO nanofluids were found to show improved thermal properties and were more resistant to HP/HT conditions than the ZnO-based NWBM. High pressure and high temperature rheological studies were conducted on NWBM at varying temperatures (25,70,90 and 110 • C) and pressures (0.1 MPa and 10 MPa). The effect of pressure on the rheology of NWBM was found to be more significant at higher temperatures.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…The work in [25] and [26] examined the use anionic NPs (nanosilica, nanotitanium and nanoaluminium). They revealed the ability of nanosilica in a concentration of 0.1 wt.% or less to improve the rheological properties and hydraulics and reduce the filtration volume and mud cake thickness.…”
Section: Fig 2 Sem Images Of the Filter Cakes After Lp/lt Filter Prementioning
confidence: 99%
“…By using commercially available silicon dioxide particles, Salih et al observed enhanced rheological and filtration properties for water based drilling muds. [32] Amanullah et al developed a nanomaterial based drilling mud with tunable rheological properties, which can be applied during and after cessation of drilling. [33] Cellulose nanoparticles (CNPs), including microfibrillated cellulose (MFC) and cellulose nanocrystals (CNCs), were shown to enhance the filtration and rheological performances of bentonite water-based drilling fluids.…”
Section: Extend Lifetime Of Equipment With Corrosion Resistancementioning
confidence: 99%